The extent to which the students of the third grade of primary school in Khamis Mushayt have the skills of reading comprehension - Al-Amir, Khalil Mohammed (Journal of Educational and Psychological Sciences, 2018)
The study aimed at measuring the extent to which the students of the third grade of the primary skills of reading comprehension. The study followed the descriptive method. The researcher designed the study tool, which is a test that was applied to the study sample which consisted of 654 students in the third grade. Of its sincerity and steadfastness. After completion of the application, the researcher used the statistical program (SPSS) including: percentages, arithmetic averages, standard deviations, and alpha kronbach. The researcher found that the level of pupils in the third grade in the reading comprehension skills and their lack of access to the level of proficiency specified in this study was (80%); the average was to enable students to understand reading comprehension as a whole (12.02) of (20) (60.10%). In the light of the results, a number of recommendations and suggestions were put forward to improve reading and increase students' understanding of the reading material.
Keywords: Empowerment; third grade of primary school; Khamis Mushait; reading comprehension